Pengaruh Motivasi Terhadap Kinerja Karyawan Pada PT. Indofood Cbp Sukses Makmur Cabang Jambi - Budi Darma (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
This study entitled The Effect of Motivation on Employee Performance at PT. Indofood CBP Sukses Makmur Jambi Branch. in this study, the expected outcome is whether or not motivation affects performance. in analyzing so the results are known, the analysis tool used is the path analysis and partial test (t test). With 56 people as samples. Based on the discussion it can be concluded that the effect of motivation on performance is 15.05%. And motivation has a partial and significant effect on employee performance at PT. Indofood CBP Sukses Makmur Jambi Branch.